Neurological complications of congenital melanocytic nevi. - Kinsler, V. (European Journal of Pediatric Dermatology, 2008)
The Author emphasizes in this long-term retrospective study the importance of neurological complications in children with congenital melanocytic nevi. These complications are more frequent in case of satellite lesions and of nevus with projected adult size >40cm.